2022
DOI: 10.1177/10693971221135703
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Models of Cultural Differences: Statistical and Theoretical Analysis

Abstract: This study finds a common statistical pattern in all major quantitative studies of cultural differences, and discusses theories that explain this pattern. 92 cultural variables from 33 published cross-cultural studies including 125 countries are analyzed with an advanced factor analysis method. The study confirms previous findings that two factors can account for a large part of the variation in all major published cultural variables. While many previously published cultural variables represent arbitrarily r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…As points out Agner Fog, "Many cultural variables are related to development, modernization, emancipation, and secularization. These factors are often strongly correlated with each other" (Fog, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As points out Agner Fog, "Many cultural variables are related to development, modernization, emancipation, and secularization. These factors are often strongly correlated with each other" (Fog, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In the latter people place a relatively high value on individual freedom and self-expression, and have activist political orientations. These are just the traits that the political culture literature characterizes as crucial to democracy (Fog, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Emancipation values are chosen because they stand for socially liberal values, which are associated with the importance attached to freedom of choice, freedom of expression and equality (Diener et al, 2013) over a strict societal order (Alexander & Welzel, 2015). It has been shown that emancipation values correlate positively with secularism (Fog, 2022) and negatively with significance attached to religious faith (Minkov et al, 2020; Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…As an alternative method, to further validate our results, we also applied factor analysis (principal component method, varimax rotation). We present the results of our factor analyses in the same way as for example Inglehart (1997, p. 82) and Fog (2022, p. 37): as figures mapping the analysed items in the set of axes presenting two factors and factor loadings determining the placement of items. Again, for better comparability, the results are rotated to align them with the background framework presented on Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Although Schwartz always presented two-dimensional solutions, we were inspired by one of our reviewers and run the analyses with different numbers of dimensions. It has been shown (Fog, 2021(Fog, , 2022Kaasa & Minkov, 2022) that in the case of factor analysis two dimensions are sufficient to cover the main cultural differences. However, Schwartz and his colleagues have not discussed the number of dimensions in the case of MDS.…”
Section: Methodsmentioning
confidence: 99%